Double Deck Trailer Design with Moving Platform for Transporting Small Livestock (Revista Cientifica Ingenio Magno, 2022)
Abstract— There was evidence of a problem in the transport of small animals, in this case goats and pigs; the use within the volume of the trailer platforms is too little for the size of the majority of trailers on the market, therefore, it was decided to design a double platform trailer in which the optimization of the size of the same vs. the number of animals to transport is better, allowing more animals per square meter, so a design method is developed evaluating different possibilities based on some border conditions that are important since the trailer will be moved by a vehicle that must be kept taking into account the cylinder capacity that relates the maximum load capacity, in addition the trailer will also transit national roads where the established traffic regulations must be met.
Keywords: Animals, pigs; double decker; sheep; transport